Image database on the WWW with postgresql object-relational DBMS: medical and GIS applications - Suwardhi, Deni; Setan, Halim; Chong, Albert K.; Majid, Zulkepli (2005)

(untitled)
This paper presents the development of a web-driven database for images. The image database archives 2-D and 3-D images. Image files are stored unchanged in a central directory (archive). Users of the system are subdivided into groups, and a user who owns an image (by uploading it) can determine specific user on the system that is allowed to view and use the image. Files can be uploaded through HTML, or using a mounted (SAMBA, NFS, etc.) drive. Entering meta-data is facilitated by user-definable templates. The meta-data fields currently in use have been designed for medical images. The meta-data fields for image in GIS are also discussed. When combined with cheap, large hard drives and a file-save backup mechanism, this image database provides a perfect means to archive images within the setting of small to medium-sized research groups. Moreover, it might be useful wherever people collaborate on images. This image database consists of PHP scripts communicating with a POSTGRESQL database. It uses MAGEMAGICK's convert to generate thumbnails from 2-D images, and EZDICOM library to generate thumbnails from 3-D images. The system has been successfully tested on WINDOWS XP Professional and LINUX (REDHAT 7.0), and should work with APACHE, PHP, POSTGRESQL and IMAGEMAGICK. Once these components are up and working, installation of this image database is simple with HTML installation form. Issues of data capture, storage, querying and retrieval in medical and GIS applications will be addressed as well.